PENGARUH PEMBUANGAN BANIR DALAM PENEBANGAN POHON TERHADAP EFISIENSI PEMUNGUTAN KAYU (Study kasus di suatu perusahaan hutan di Kalimantan Barat) - Sona Suhartana; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1995)
This paper presents  the results  of the study  of  the  impact of buttress cutting in tree felling on harvestring efficiency.  The case study was carried  out in PT Kurnia   Kapuas Plywood in West Kalimantan in  1994.  771e aim of the  study is to know the influence of buttress cutting on wood haversting efficiency.the  data were analysed by using  the I-test.the result of study shows that average of wood harvesting efficiency by cullting buttress is 68.1 % and without cutting buttress is 66.7 %